Perubahan Sosial Dalam Pandangan Ali Syari’ati - Arsyad (Budapest International Research and Critics University, 2017)
This essay describes about Ali Shari'ati’s view on social change. Shari’ati isone of the sociological figures based on the Islamic philosophy paradigminstead of looking at social society differently from the perspective ofWestern sociologists. Shari'ati laid down the values or ideology he embracedas the paradigm of understanding social facts, and of course Shari'ati placedhumans as human beings. Man in Shari'ati's view is a two-dimensionalhuman, that is, the dimension of physics and dimension of sedimentary land.